Supply chain readiness, response and recovery for resilience - Chowdhury, M.; Quaddus, Mohammed (2016)
© 2016, © Emerald Group Publishing Limited.Purpose: Despite the proliferation of supply chain risk management (SCRM) studies, a theoretically supported and empirically validated study on justifying the antecedents and measurement dimensions of supply chain resilience (SCRE) is rare. Therefore, drawing on extensive literature review, this study aims to explore and validate the antecedents and the measurement dimensions of SCRE. Design/methodology/approach: This study uses positivist paradigm using quantitative method. However, it also uses qualitative approach in the form of field study to contextualize the research model. The quantitative study is conducted by operationalising a survey research. Partial least square-based structural equation modelling has been used to analyze the data. Findings: Study results suggest that the psychometric properties of the SCRE dimensions, supply chain readiness, response and recovery, are reliable and valid. It also affirms that supply chain orientation (SCO), learning and development and supply chain risk management culture (SCRMC) significantly influence the SCRE. Further, SCRMC mediates the relationship between SCO and SCRE. Practical implications: The findings of this study will assist the supply chain managers in taking decision on readiness capability development and reducing the decisional uncertainty during response and recovery. Originality/value: Drawing on extensive extant literature on crisis management and supply chain management, this study develops and validates the measurement dimensions of SCRE in terms of readiness, response and recovery, as well as justifies the antecedent factors of SCRE, which is a novel attempt in SCRM literature.